The Ongoing Myanmar’s Religious and Ethnic Crises: Lessons from Medina’s Constitution - Fadzli, Adam; Fakhratu Naimah, Muhad Adam (2017)
The issue pertaining religious crises and genocide are not recently created but grounded on this earth for centuries. Nonetheless, this problem finds no concrete solution as the crises are apparently unstoppable. Recently, the crisis of bloody Myanmar has turning on the attention of the world for the violation of human rights, brutalities, blood-shed and inhumane acts done. Hence, this conceptual paper is responding to the above-mentioned crises by the approach of replicating the Constitution of Medina and related Islamic political law. Referred to the successfulness of this constitution in maintaining the stability of Medina, it is hope for a new Myanmar to find its solution for the current and future betterment. Using a secondary analysis, published materials written by the writers and scholars in the field, some stances, and analysis of scholars are reviewed and analyzed. Notwithstanding of abundances of solutions and proposals theorized in solving this issue, yet, it is a hope that this written idea can receive consideration to be one of the supportive influences in bringing the new harmonious and beautiful co-existence living within the whole communities of Myanmar.